Mass Renormalization in the Nelson Model - Fumio Hiroshima; Susumu Osawa (International Journal of Mathematics and Mathematical Sciences)
The asymptotic behavior of the effective mass meff(Λ) of the so-called Nelson model in quantum field theory is considered, where Λ is an ultraviolet cutoff parameter of the model. Let m be the bare mass of the model. It is shown that for sufficiently small coupling constant α of the model, meff(Λ)/m can be expanded as meff(Λ)/m=1+∑n=1∞an(Λ)α2n. A physical folklore is that an(Λ)=O(logΛ(n-1)) as Λ→∞. It is rigorously shown that 0<limΛ→∞a1(Λ)<C,  C1≤limΛ→∞a2(Λ)/log⁡Λ≤C2 with some constants C, C1, and C2.